Epidemiologija, etiopatogeneza in histološka klasifikacija pljučnih tumorjev - Rott, Tomaž (Medicinski razgledi, 2002)
Lung cancer is the most frequent type of malignant disease among men. It is also the leading cause of cancer deaths among both men and women. Annually, there are over 8 million new cases and over one million deaths worldwide due to lung cancer. Smoking is a contributing factor in about 90% of men and 78% of women in these cases, while other cases are believed to be caused by occupational or environmental exposure to various noxious agents, pulmonary fibrosis and genetic factors. From 1995 to 1998, the incidence of lung cancer in Slovenia among men decreased from 88.3 to 82 per 100,000; there was also a decrease in the percentage of lung cancer among all malignant diseases, from 22 to 19%. During the same period, the incidence of lung cancer among women increased to 19 in 100,000, representing 5% of all malignant diseases. Limitedlung cancer, locally spread lung cancer, lung cancer with distant metastases and undetermined stages of lung cancer represented 25%, 38%, 34% and 3% of cases, respectively. In 1998, 82.9% of lung cancer cases presented histologically as non-small cell lung cancer. Small-cell lung cancer with a very unfavorable prognosis was found in the remaining 17.1%. In the last two decades, the incidence of adenocarcinoma has increased. The overall 5-year survival rate was 8% for men and 10% for women, but over 60% for stage I of the disease. The latest classification of lung tumors distinguished other unfavorable histological types and subtypes of non-small cell lung cancer, such as pleomorphic and combined large cell neuroendocrine cancer, which represent about 10% of cases. Synchronous and metachronous double primary lungtumors were detected in 8.4% of cases in the lungs and at other locations in 11%, and triple primary tumors in 0.8% of cases. Various tumor and non-tumor synchronous multiple pathological changes in the lungs were found in18% of cases.
Keywords: Adenoma; Lung Neoplasms; Bronhialne novotvorbe; Epidemiology; Etiology; Pljučne novotvorbe; Pathology; Prekanceroze; Precancerous Conditions; Adenomatoza pljučna; Papilloma; Karcinoidni tumor; Karcinom drobnocelični; Bronchial Neoplasms; Adenomatosis, Pulmonary; Karcinom nemalocelični, pljučni; Karcinom ploščatocelični; Carcinoma, Squamous Cell; Carcinoma, Small Cell; Mezoteliom; Paraneoplastični sindromi; Carcinoma, Non-Small-Cell Lung; Carcinoid Tumor; pljučni rak; novotvorbe; Mesothelioma; tumor; Paraneoplastic Syndromes; epidemiologija; etiologija; Adenom; histologija; Papilom; diagnostika